Від реституції – до спільного користування інформацією - Шумейко, М. (Архіви України, 2008)
The article highlights the measures taken by Belarusan archivists together with museum workers and librarians aimed at restitution of cultural values of Belorussia origin. The matter concerns, in particular, secondary information exchange (in the form of descriptive lists, information about the fonds structure and contents, reference books etc.) with specialized foreign archives, joint preparation of reference books on foreign archives fonds, documentary editions etc.